1986
DOI: 10.1002/path.1711500303
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical demonstration and significance of p21 ras family oncogene product in benign and malignant breast disease

Abstract: It has been suggested that the immunocytochemical demonstration of the p21 ras oncogene product is a useful marker of malignancy in breast disease. We have studied the reactivity of a series of specimens of benign and malignant breast disease with the anti ras p21 monoclonal antibody Y13-259, and shown widespread positive staining in both benign and malignant (including metastatic) disease as well as in adjacent 'normal' epithelium. In addition some staining of stromal cells as well as nerve fibres was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Besides specific immunohistochemical staining in tumor cells, we found a consistent and specific, albeit less intense, intracytoplasmic staining in benign cells. This has also been reported by others [15,[17][18][19][20]. Gutheil et al [27] attributed it to cross-reaction of the antibodies used and did not take into consideration the physiologic function of p21 in nondiseased cells.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Besides specific immunohistochemical staining in tumor cells, we found a consistent and specific, albeit less intense, intracytoplasmic staining in benign cells. This has also been reported by others [15,[17][18][19][20]. Gutheil et al [27] attributed it to cross-reaction of the antibodies used and did not take into consideration the physiologic function of p21 in nondiseased cells.…”
Section: Discussionsupporting
confidence: 55%
“…Expression of ras proteins has hitherto been tested by RNA hybridization [7][8][9][10]. Western blotting [11][12][13], radioimmunoassay [14,15] or immunohistochemistry [16][17][18][19][20]. These studies provided evidence that, as in colon carcinoma [21], Hras may play an important and initial role during the multistep carcinogenesis of breast cancer.…”
Section: Introductionmentioning
confidence: 90%
“…Both benign and malignant breast lesions have demonstrated an elevated level of K-ras and N-ras mRNA and protein levels (11,26), and it is of particular interest that high levels of ras protein were found in benign breast specimens in patients who subsequently developed cancer (12). However, conflicting results have been reported by several investigators (13,14).…”
Section: Discussionmentioning
confidence: 96%
“…Several studies of both qualitative (structural mutation) and quantitative (altered levels) aspects of ras family oncogene expression in different tumor types, including SCCHN, have been reported (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In this prospective study we have examined the relationship of H-ras, K-ras, and N-ras oncogene expression in squamous cell carcinoma of the head and neck (SCCHN) to the various clinicopathologieal parameters of these tumors.…”
mentioning
confidence: 99%
“…Ras mutations are rare in breast carcinomas (Rochlitz et al, 1989) and gene amplification has not been recorded, but there are conflicting observations (reviewed by Field ) of ras protein expression. Hyperexpression has often been recorded (Spandidos & Agnantis, 1984;Ohuchi et al, 1986;De Bortoli et al, 1985;Clair et al, 1987;Fromowitz et al, 1987), but some immunocytochemical studies with the antibodies RAP-5 (Ghosh et al, 1986) and Y13-259 (Candlish et al, 1986;Walker & Wilkinson, 1988) have found no increased reactivity in carcinomas compared with benign parenchyma. Walker and Wilkinson (1988) suggested that expression in carcinomas was actually less than in normal parenchyma.…”
mentioning
confidence: 99%